Rückwirkung und Vertrauensschutz im Recht der Energiewende: zu den verfassungsrechtlichen Grenzen von Gesetzesänderungen im Rahmen der Energiewende am Beispiel der § 17e Abs. 2 und 5 EnWG - Grzeszick, Bernd (Energierecht, 2018)
The energy turnaround has put the protection of the laws validity to the test, begging the question: Should legislation changed at the end of 2012 be applied in cases where grid operator liability has been transferred to, say, the operator of an offshore wind farm that was still under construction at that time? And to what extent does constitutional law object to a change in liability law?